Performance Assessment & Ductility Enhancement of Beams Subjected to Cyclic Loading - Daali, Larbi Mohamed (My University, 1995)
Structural frames designed or proportioned to resist seismic forces, must possess adequate ductility to redistribute internal forces or have needed energy absorbing capability. This research investigation touches on a number of aspects that deal with or relate to the above characteristics, while the principal aim is to assess and compare the rotation capacity and energy absorption of locally web stiffened beams with unstiffened beams.
An approach which allows for the prediction of the initiation of local buckling in the design of wide-flanged beams under moment gradient, is first presented. The method described represents a refined moment-rotation model that includes the effects of strain hardening. This same approach helps define more accurately the appropriate slenderness limits of a beam's plate-elements in relation to the required rotation capacity at maximum moment.
The study then addresses the interaction effects of a steel member's plate slenderness values and its lateral slenderness on rotation capacity at ultimate deformation. It is shown that members with slenderness values close to the limits specified by codes of practice may not be able to redistribute moments adequately under seismic loading.
To further ascertain and assess the ductility and energy dissipation capabilities of W-shaped beams, a series of test specimens subjected to monotonic and quasi-static cyclic loading was conducted. The specimens were meant to represent beams in ductile moment resisting frames undergoing cyclic lateral loads. Of direct relevance to seismically designed moment resisting steel frames, the experimental results of this research effort clearly highlight the superiority of herring-bone style stiffened specimens over unstiffened specimens. To provide further supporting evidence, as well as insights into the behaviour of herring-bone stiffeners, an inelastic large deformation analytical study was undertaken using cubic-quadratic shell finite elements. This work allowed a parametric study to be undertaken on the effects of stiffener thickness on strength and ductility properties. Based on these, and the experimental results, preliminary design guidelines have been proposed. Another important objective was to assess and document the strength and energy deterioration occurring under conditions of low cycle fatigue and which involve local buckling.
The results of a series of W-shaped test specimens subjected to fatigue type of loading under constant amplitude are presented. This work has permitted strength and energy deterioration and damage models to be developed for the W-shape steel beams. A generalized model which uses plate slenderness values together with lateral slenderness is proposed for predicting the rate in strength deterioration per reversal and cumulative damage after a given number of reversals.
The research investigation concludes with a review of some of the concepts used in damage assessment; simple damage parameters such as ductility ratio and realistic mathematical models reflecting the deterioration of steel beams due to maximum response, and, dissipated energy are then discussed. Damage models are then presented that combine maximum response with repeated effects in low-cycle fatigue loading. The proposed models calibrated through the use of cyclic tests on steel beams, are then used to yield deterministic parameters that predict adequate ductility values for steel beams under cyclic loading. This phase of the work was completed by having the damage models incorporated into a non-linear dynamic analysis of a sample building and ends with the recommendation of employing a new "adequate ductility" design parameter.
Keywords: Civil Engineering; Civil Engineering